2013
DOI: 10.1074/jbc.m112.408039
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the DNA-binding Domain Tetramer of the p53 Tumor Suppressor Family Member p73 Bound to Different Full-site Response Elements

Abstract: Background: Members of the p53 protein family bind to full-site response elements (REs) to trigger specific cellular pathways. Results: We solved two crystal structures of the p73 DNA-binding domain in complex with full-site REs. Conclusion: Lys-138 in loop L1 distinguishes between consensus REs. Significance: Conformational changes in Lys-138 might explain specificity between cell arrest and apoptosis target genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 44 publications
1
34
0
4
Order By: Relevance
“…Common to these complexes and the 20-bp:AcK120 complex, is the conformational switch of loop L1 and loss of K120 interaction with the DNA (K138 in p73). In addition, previous studies suggested that the flexibility of loop L1 is important for sequence specific target recognition of the p53 family, and promotes the induction of apoptosis [37,38,[41][42][43]. The structural data presented here show that K120-acetylation increases the flexibility of loop L1 which may contribute in a similar way to more specific target recognition and p53 transcriptiondependent induction of apoptosis.…”
Section: Discussionmentioning
confidence: 48%
“…Common to these complexes and the 20-bp:AcK120 complex, is the conformational switch of loop L1 and loss of K120 interaction with the DNA (K138 in p73). In addition, previous studies suggested that the flexibility of loop L1 is important for sequence specific target recognition of the p53 family, and promotes the induction of apoptosis [37,38,[41][42][43]. The structural data presented here show that K120-acetylation increases the flexibility of loop L1 which may contribute in a similar way to more specific target recognition and p53 transcriptiondependent induction of apoptosis.…”
Section: Discussionmentioning
confidence: 48%
“…As observed before for five structures of WT p73 DBD bound to different DNAs (26), each monomer recognizes a ¼-site RE. In the rest of the description, we compare the structure of the S139F mutant with the structure of the WT bound to an identical 20mer GAACA full-site (PDB ID: 4g82) because both crystals have the same space group, unit cell dimensions and crystal packing (34). Moreover, the asymmetric unit in the crystals for both proteins, the WT and the S139F mutant, has a dimer with half-site RE.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, although in WT p73 the terminal amine of K138 is 3.8 Å from the oxygen in the phosphate backbone, in the S139F mutant, K138 is significantly displaced and cannot form the same interactions as in the WT. The p73 WT DBD–20mer complex structure is deposited in the PDB with ID: 4g82 (34), and the p73 S139F DBD–20mer complex structure is deposited in the PDB with ID: 4guq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations